Eroica e poetica pedagogica - Maria D'Ambrosio (Firenze University Press, 2019)
The 'nourishment', the relationship, the encounter, the relationship with the origins, are investigated in the writing and recognized as a vital necessity, whose ways and forms are looked over but whose outcomes remain unpredictable. Moving and going through one's own existence as a Wandering, even the questions relating to one's origins weaken and become more significant instead those relating to heroes and 'masters', to those generative encounters, which constitute the pragmatic plastic of becoming and figuration of a romantic heroic and pedagogical poetic. A reflection that intersects the questions of the contemporary becoming, of the post-human, which recognizes in the journey still the metaphor of a formation conceived as a transformation and as a path/process that passes through the encounter with the other and can change itself in somewhere else.